Soils, climate & society: archaeological investigations in ancient America - Wingard, John D., editor; Hayes, Sue Eileen, editor; University Press of Colorado, publisher (Colorado State University. Libraries, 2013)
Much recent archaeological research focuses on social forces as the impetus for cultural change. Soils, Climate, and Society, however, focuses on the complex relationship between human populations and the physical environment, particularly the land--the foundation of agricultural production and, by extension, of agricultural peoples. This volume traces the sociocultural implications of agriculture, agriculture's effects on population, and the theory of carrying capacity, considering the relation of agriculture to the profound social changes that it wrought in the New World. Soil science plays a significant, though varied, role in each case study and is the common component of each analysis. Contributors use information derived from dendrochronology, ground-penetrating radar, soil chemistry, and meteorological records, along with a variety of analytical techniques and computer simulations to determine the amount of food that can be produced in a particular soil and the effects of occupation and cultivation on that soil. They also consider the resulting consequences for future cultivators. Soils, Climate, and Society demonstrates that renewed investigation of agricultural production and demography can answer questions about the past, as well as stimulate further research. It will be of interest to scholars of archaeology, historical ecology and geography, and agricultural history.--Provided by publisher.
Introduction: a user's guide to soils, climate, and society / Sue Eileen Hayes and John D. Wingard -- Population estimates for anthropogenically enriched soils (Amazonian dark earths) / William I. Woods, William M. Denevan, and Lilian Rebellato -- Soilscape legacies: historical and emerging consequences of socioecological interactions in Honduras / E. Christian Wells, Karla L. Davis-Salazar, and David D. Kuehn -- Drought, subsistence stress, and population dynamics: assessing Mississippian abandonment of the Vacant Quarter / Scott C. Meeks and David G. Anderson -- Mimbres mogollon farming: estimating prehistoric agricultural production during the classic Mimbres period / Michael D. Pool -- So who's counting?: modeling pre-Columbian agricultural potential in the Maya world / Sue Eileen Hayes -- Tilling the fields and building the temples: assessing the relationship among land, labor, and classic Maya elite power in the Copán Valley, Honduras / John D. Wingard -- An EPIC challenge: estimating site population in south coastal Peru / Sue Eileen Hayes -- Feeding the masses: new perspectives on Maya agriculture from Cerén, El Salvador / Christine C. Dixon -- How can we know?: the epistemological foundation of ecological modeling in archaeology / Sissel Schroeder.
Keywords: Indians -- Agriculture; Soil science in archaeology -- America; Human ecology -- America; Agriculture, Prehistoric -- America